Current Topics on Superfoods 2018
DOI: 10.5772/intechopen.74084
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds Contained in Mediterranean Diet and Their Effects on Neurodegenerative Diseases

Abstract: Neuroinflammatory processes in the brain are believed to play a crucial role in the development of neurodegenerative diseases, especially due to increased production of reactive oxygen species. The brain is susceptible to oxidative stress more than other organs due to the low activity of antioxidant defense systems. In agreement with these observations, increased oxidative stress plays an important role in the pathogenesis of neurodegenerative diseases such as Alzheimer disease, Parkinson disease, ischemic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…The MedDiet contains a multitude of bioactive compounds such as melatonin, phytosterols, carotenoids and polyphenols (e.g. resveratrol and hydroxytyrosol) [8], many of which exert a protective effect against genomic instability by preventing DNA damage, enhancing DNA repair, or attenuating telomere shortening (see Telomere Attrition). These effects appear to be related to the anti-inflammatory effects of the MedDiet (see Altered Intercellular Communication), but also may be due to changes in gene expression induced by the MedDiet directly [23][24][25], or via epigenetic mechanisms [26].…”
Section: Genomic Instabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The MedDiet contains a multitude of bioactive compounds such as melatonin, phytosterols, carotenoids and polyphenols (e.g. resveratrol and hydroxytyrosol) [8], many of which exert a protective effect against genomic instability by preventing DNA damage, enhancing DNA repair, or attenuating telomere shortening (see Telomere Attrition). These effects appear to be related to the anti-inflammatory effects of the MedDiet (see Altered Intercellular Communication), but also may be due to changes in gene expression induced by the MedDiet directly [23][24][25], or via epigenetic mechanisms [26].…”
Section: Genomic Instabilitymentioning
confidence: 99%
“…The beneficial effects of the MedDiet on mitochondrial function, are related, at least in part, to the high content of antioxidants and bioactive polyphenols derived from foods such as red wine, olive oil, fruits and vegetables [8]. Recently Varela-Lopez et al demonstrated that olive oil had a beneficial impact on mitochondrial structure, function, as well as oxidative stress level in older rats [102].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both technological and agronomic processes applied to berries and the low content of RSV are limiting factors for considering berries as a significant source for this bioactive compound. Similarly, other foods contain small quantities of RSV, such as peanuts, dark cocoa, beer and beeswax from honeycomb [159].…”
Section: Resveratrol (Rsv)mentioning
confidence: 99%
“…Further studies are needed to confirm their beneficial effect in humans. At the moment, the strongest recommendation in behavioral and nutritional terms-when a good cognitive reserve still remains-is to adopt an active lifestyle together with a diet with the characteristics of the Mediterranean diet (possibly enriched with walnuts and olive oil) [22][23][24]159,188,189,247,269]. Recently, Ravi et al [394] emphasize how Mediterranean diets, mainly composed of fruits, vegetables and omega-3 fatty acids, stand as valuable, mild and preventive anti-AD agents, able to fight this devastating neurodegenerative disorder through the simple proper modification of our life style.…”
Section: The Research Continuesmentioning
confidence: 99%